To study the clinical profile of chronic kidney disease and associated comorbidities in geriatric patients - Pathak, Ashvani; Jain, Lalit; Jaiswal, Praveen (International Journal of Research in Medical Sciences, 2017)
Background: Chronic kidney disease (CKD) has become a major issue in our nation. CKD does not have a specific target, but individuals with diseases such as diabetes mellitus, cardiovascular disease, and obesity are all at increased risk. The chronic kidney disease (CKD) is associated with many features like hyperkalemia, hypocalcemia, hyponatremia, anaemia, hypoalbuminemia, high blood pressure etc. So if we detect all these features early, we can extend the quality life of CKD patients. Aim and objectives of the study were early detection of CKD in elderly people at Initial stage to prevent progression of disease, to study the clinical and biochemical profile and co-morbidities in elderly people with CKD. Methods: This Hospital based descriptive study was done in the Department Of Medicine, NSCB Medical college, Jabalpur from October 2014 to October 2015 including 100 patients of 60+ years of age. Results: In present study the etiology of chronic kidney disease was diabetes in 45.0%, hypertension in 38.0%, obstructive uropathy in 8.0% and undetermined etiology was 9.0%. Cardiovascular disease was present in 28% cases, stroke in 22% cases. Most common clinical features was dyspnoea [63.0% (p<0.001)] pedal oedema (31%), high blood pressure [54.0% (p<0.001)], pallor [49.0% (p<0.001)], and pedal oedema (31.0%).The abnormality in the laboratory profile was dyslipidemia in 73% hypoalbuminemia in 31.0% (p<0.05), albuminuria in 73.0% (p<0.001), hypocalcemia in 54.0% (p<0.001), hyponatremia in 23.0%, hyperkalemia in 14%, anemia in 60.0% (p<0.05). LVH on echocardiography is present in 34.0% (p<0.05) cases. Conclusions: The major causes of CKD in descending order were, type 2 diabetes mellitus, hypertension, and obstructive uropathy. All these features needs prompt detection and correction at earlier stages of CKD to delay progression and reduce associated morbidity and exacerbating factors and to prevent early mortality.